Сатисфакция: сценарий, пьесы и лирика / Евгений Гришковец - Гришковец Евгений Валерьевич (Махаон, 2011)
Экземпляры: ф. 2 (20130916) / Инвентарный номер: 100039 / Цена: 247.00 / Авт.знак: Г 85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6